Oral health status and treatment needs among 5–15-year-old children of tribal population in Noolpuzha Panchayath of Wayanad: A cross-sectional study - M. T. Jeseem; Soumya Mohanan Thotten Veetil; Kannan Vadakkepurayil; Muhammed Rasif Manningal (Journal of Indian Society of Pedodontics and Preventive Dentistry)
Context: There is a decreased quality of oral health among tribal communities as well as a paucity of research in this field. Their poor accessibility to dental resources results in an increased prevalence of dental diseases in them. Aims: The aim of this study was to assess the oral health status and treatment needs among the tribal children in Noolpuzha panchayath of Wayanad district of Kerala state. Settings and Design: This was a cross-sectional survey among 1158 children aged 5–15 years of tribal communities by a single examiner. Subjects and Methods: The oral health status was determined using a modified WHO Oral Health Assessment Form 2013 for children. The caries status was assessed using decayed, missing and filled (dmf) and Decayed, Missing, Filled (DMF) and the gingival condition using the Modified Gingival Index. The subjects were interviewed with a validated WHO Oral Health Questionnaire 2013 for children. Statistical Analysis Used: SPSS software 25.0 was employed to analyze the data. The data analysis includes descriptive statistics, Chi-square test for qualitative variables, t-test/analysis of variance test, and post hoc tests for comparing quantitative variables between the subgroups. Results: The mean DMF Teeth (DMFT) and dmft value was 0.72 ± 1.3 and 1.85 ± 2.7, respectively. The prevalence of mild, moderate, and severe gingivitis was found to be 54.9%, 23.3%, and 2.8%, respectively, with an overall prevalence of gingivitis of 81%. Among the subjects, 9.6% had enamel hypoplasia, 5.4% had traumatic dental injuries, 5.2% had oral mucosal lesions, and 21.1% had oral habits. The children with tobacco smoking and tobacco chewing habits were 1.5% and 15.7%, respectively. The dental treatment need was 82.8%. Conclusions: The present study revealed a high treatment need for the tribal community, with a relatively higher prevalence of gingivitis and noticeable number of dental caries, oral lesions, traumatic dental injuries, enamel hypoplasia, sugar consumption, and tobacco smoking/tobacco chewing habits.